Gogol and Shevchenko in a foreign transcription (Literatures of the World: Poetics, Mentality and Spirituality, 2016)
This article discusses deficiencies in stylistic studies of Gogol and Shevchenko. The author highlighted to these prevailing issues in connection with the 200th anniversary of both Ukrainian writers, also it was pointed out in the discussion about how they belong to different stylistic periods and national literatures. The author also touched upon the issue of perception of literary creativity of writers abroad.
Keywords: creative style; national characteristics; baroque; romanticism; realism; folklore; literature abroad